Role of Salt Migration in Destabilization of Intra Permafrost Hydrates in the Arctic Shelf: Experimental Modeling - Evgeny Chuvilin; Valentina Ekimova; Boris Bukhanov; Sergey Grebenkin; Natalia Shakhova; Igor Semiletov (Geosciences, 2019)
Destabilization of intrapermafrost gas hydrate is one possible reason for methane emission on the Arctic shelf. The formation of these intrapermafrost gas hydrates could occur almost simultaneously with the permafrost sediments due to the occurrence of a hydrate stability zone after sea regression and the subsequent deep cooling and freezing of sediments. The top of the gas hydrate stability zone could exist not only at depths of 200–250 m, but also higher due to local pressure increase in gas-saturated horizons during freezing. Formed at a shallow depth, intrapermafrost gas hydrates could later be preserved and transform into a metastable (relict) state. Under the conditions of submarine permafrost degradation, exactly relict hydrates located above the modern gas hydrate stability zone will, first of all, be involved in the decomposition process caused by negative temperature rising, permafrost thawing, and sediment salinity increasing. That’s why special experiments were conducted on the interaction of frozen sandy sediments containing relict methane hydrates with salt solutions of different concentrations at negative temperatures to assess the conditions of intrapermafrost gas hydrates dissociation. Experiments showed that the migration of salts into frozen hydrate-containing sediments activates the decomposition of pore gas hydrates and increase the methane emission. These results allowed for an understanding of the mechanism of massive methane release from bottom sediments of the East Siberian Arctic shelf.